Constitutive NF-kappaB activity in colorectal cancer cells: impact on radiation-induced NF-kappaB activity, radiosensitivity, and apoptosis - Voboril, R; Weberova-Voborilova, J (Neoplasma, 2006)
Constitutive NF-kappaB activity has been found in many cancer cells of different origin. In our study we focused on constitutive NF-kappaB activity and its impact on radiation-induced NF-kappaB activity, intrinsic radiosensitivity, and apoptosis. Using colorectal cancer cell lines (Caco-2, SW480, SW620) we demonstrated that each cell line expresses different level of constitutive NF-kappaB activity. Moreover, irradiation caused secondary NF-kappaB activation which differed in each cell line. The cell lines tested displayed also different intrinsic radiosensitivities as was determined by clonogenic assay, and different spontaneous and radiation-induced apoptosis determined by activity of caspase 3. Complex analysis of our results revealed that there was a strong correlation between constitutive NF-kappaB activity and radiation-induced NF-kappaB activity (r=0.835), the level of constitutive NF-kappaB activity predicted the level of secondary, radiation-induced NF-kappaB activity. Furthermore, SW620 cells with the highest level of constitutive NF-kappaB activity displayed the lowest radiosensitivity and the lowest level of spontaneous apoptosis; Caco-2 cells with almost undetectable level of constitutive NF-kappaB activity displayed the highest radiosensitivity and even highest level of spontaneous apoptosis. SW480 cells showed intermediate level of constitutive NF-kappaB activity, intermediate radiosensitivity and intermediate level of spontaneous apoptosis. Our data suggest that the level of constitutive NF-kappaB activity may predict radiosensitivity of colorectal cancer cells. Such prediction may allow the individualization of patient treatment by radiotherapy.
Keywords: NF-kappa B; Colorectal Neoplasms; Dose-Response Relationship, Radiation; Apoptosis; Humans; Electrophoretic Mobility Shift Assay; Tumor Cells, Cultured; lidé; nádorové buňky kultivované; vztah dávky záření a odpovědi; Adenocarcinoma; kaspasy; radioizotopy kobaltu; apoptóza; kolorektální nádory; Cobalt Radioisotopes; Caspases; retardační test; adenokarcinom; Radiation Tolerance; tolerance záření